The Contestation of Values in Character Education: Political Interest and School Burden - ., Supardin; Arkan Syafera, Irwan Abdullah; Jubba, Hasse; Insawan, Husain (Opción, 1970)
This paper discusses the issue of character education in Indonesia, which has not met expectations. In detail, this paper analyzes how schools' status as subordinate to the state burdens them with specific ideologies that influence how they undertake their educational mission. The contestation of values within schools' curricula deleteriously affects students' character development. Data were obtained through field observations at three schools, as well as interviews with principals, teachers, and students to obtain information regarding the implementation and perception of character education. This study finds that schools have become arenas for the contestation of values, and this contestation of values results in conflict as students develop their character. It recommends that character education accommodate students' perspectives by recognizing their socio-cultural diversity; it should also avoid the undue influence of outside interests. Even though schools are administratively extensions of the state, they should not become propaganda tools that simply promote state interests.